Digital Islamic Preaching and the Construction of Religious Tolerance: A Strategic Management Perspective - Siti Fatimah Azzahra; Syarifah Haniyah; Lidya Safitri; Putri Putri; Hairus Soleh (Islam and Social Sciences Review, 2026)
The rapid expansion of digital media has transformed Islamic preaching (da'wah) practices, creating new opportunities and challenges in communicating religious tolerance within increasingly pluralistic societies. While previous studies have examined digital da'wah and religious moderation separately, limited attention has been given to how strategic da'wah management constructs and communicates the concept of religious tolerance through digital platforms. This study addresses this gap by investigating the strategic management of digital da'wah in promoting religious tolerance through Buya Yahya's sermons on the Al-Bahjah TV YouTube channel. Employing a qualitative content analysis, the study systematically analyzed selected sermon transcripts focusing on narratives concerning interfaith relations and the boundaries of religious tolerance in Islam. To enhance analytical validity, the findings were triangulated with semi-structured interviews conducted with Muslim informants from Hadhramaut, Yemen. The findings reveal that the da'wah strategy is characterized by three interconnected dimensions: (1) conceptual clarification of religious tolerance as respect for religious diversity without compromising Islamic creed (aqidah); (2) persuasive and contextual communication that addresses contemporary misconceptions surrounding interfaith engagement; and (3) strategic utilization of digital media to broaden audience reach while maintaining doctrinal consistency. The study further demonstrates that digital da'wah contributes to fostering a balanced understanding of religious tolerance by integrating harmonious social relations with firm religious commitments. These findings extend the literature on strategic religious communication by proposing a conceptual framework for digital da'wah management that combines theological authenticity, contextual communication, and digital engagement. The proposed framework provides practical implications for religious communicators, Islamic institutions, and policymakers seeking to promote moderate religious discourse in the digital era.